Implementasi Fitur Instagram Reels Sebagai Media Penyuluhan Ajaran Tri Hita Karana Di Era Society 5.0 - I Dewa Gede Darma Permana (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The popularity of the Instagram Reels feature in the current Society 5.0 era can be considered high. This phenomenon cannot be separated from the rapid development of technology. Therefore, the Instagram Reels feature can be used positively in socializing the teachings of Tri Hita Karana. In terms of axiology, Tri Hita Karana is a noble teaching of Hinduism, especially Bali, which is useful in maintaining harmony between people in the midst of competitive times. Based on this populist phenomenon, researchers on this occasion are interested in comprehensively examining the implementation of the Instagram Reels feature as a medium for counseling the teachings of Tri Hita Karana. To support this goal, three problem formulations are presented, among others: about the popularity of the Instagram Reels feature, the virtues of the Tri Hita Karana teachings, and the implications of the Instagram Reels feature as a medium for counseling the Tri Hita Karana teachings. The method used in this research is a type of qualitative research that further uses a visual ethnography approach. This research shows that, the implementation of the Instagram Reels feature as a medium for counseling the teachings of Tri Hita Karana has the advantage of unique, creative video production, as well as in terms of more efficient and effective promotion of the noble teachings of Tri Hita Karana as a noble philosophical teaching in creating a harmonious life in the era of Society 5.0.